2023
DOI: 10.1212/wnl.0000000000207240
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Features of Cluster Headache and Migraine

Abstract: Background and objectives:Cluster headache and migraine have circadian features at multiple levels (cellular, systems, and behavioral). A thorough understanding of their circadian features informs their pathophysiologies.Methods:A librarian created search criteria in Medline Ovid, Embase, PsycINFO, Web of Science, and Cochrane Library. Two physicians independently performed the remainder of the systematic review/meta-analysis using PRISMA guidelines. Separate from the systematic review/meta-analysis we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…As previously documented for cluster headache, this meta-analysis 6 found that a circadian pattern of attack was prominent, noted in 70.5% cases; attacks most commonly occur during the evening, with a peak at 2 AM. A circadian pattern also featured in 50.1% of participants with migraine, with most attacks occurring during the day, between late morning and early afternoon.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…As previously documented for cluster headache, this meta-analysis 6 found that a circadian pattern of attack was prominent, noted in 70.5% cases; attacks most commonly occur during the evening, with a peak at 2 AM. A circadian pattern also featured in 50.1% of participants with migraine, with most attacks occurring during the day, between late morning and early afternoon.…”
supporting
confidence: 76%
“…Hypothalamic activation plays a role in both types of headache, 2,3 and given the role of the hypothalamus in regulating both circadian and headache-relevant homeostatic functions in the brain, it is perhaps not surprising that some headache disorders display circadian features and may be underpinned by chronobiological factors. 4,5 In this issue of Neurology ® , Benkli et al 6 present a systematic literature review and meta-analysis of the current knowledge of a variety of circadian features in relation to cluster headache and migraine, including observations of headache chronobiology, circadian-associated hormonal and gene expression of susceptibility loci across tissues, and associated genetic variants in core clock genes.…”
mentioning
confidence: 99%
See 3 more Smart Citations